Efektivitas Pendekatan Contextual Teaching and Learning Berbantuan Media Manipulatif Jaring-Jaring Kubus dan Balok terhadap Hasil Belajar Siswa Kelas VI SD - Riskianti, Riskianti; Sirajuddin, Sirajuddin; Hadaming, Hamdana (Jurnal Gentala Pendidikan Dasar, 2026)
A study was conducted on the effectiveness of the Contextual Teaching and Learning (CTL) approach, supported by manipulative media such as cube and rectangular prism nets, on the mathematics learning outcomes of sixth-grade elementary school students. This study was motivated by the low learning outcomes of students on the topic of cube and rectangular prism nets, which resulted from teaching that remained teacher-centered and the minimal use of concrete media. This study employed a quantitative approach using a Pre-Experimental Design with a One-Group Pretest-Posttest design, involving 22 sixth-grade students at SD Negeri No. 10 Galung. The results showed an increase in the average pretest score from 49.09 to 80.45 on the posttest, a classical mastery rate of 77.3%, a significance value of 0.000 (< 0.05), and an N-Gain of 0.62, categorized as moderately effective. Additionally, student learning activities reached the active category with an average of 61.18%, and student responses were in the very good category with a percentage of 82.57%. These findings indicate that the implementation of the Contextual Teaching and Learning (CTL) approach aided by manipulative media is effective in improving students’ mathematics learning outcomes and creating contextual, concrete, and meaningful learning.